The Transformation of Islamic Art during the Sunni Revival: By Yasser Tabbaa (Seattle and London: University of Washington Press, 2001. 210 pages.) (American Journal of Islam and Society, 2003)
The Islamic world underwent profound political and religious changes in theeleventh and twelfth centuries. These changes were paralleled by one of themost significant transformations of Islamic art and architecture. What shared meaning lies at the origins of these two historical developments? How, if atall, were these paralleled transformations part of the same struggle?The Transformation of Islamic Art during the Sunni Revival takes usinto this dialogue. This work consists of seven chapters, including aplethora of beautiful photographs, in which Yasser Tabbaa, a professor at theUniversity of Michigan and a highly regarded Islamic art scholar, argues thatthe transformations in medieval Islamic architecture and ornament duringthis period reflected and embodied the conflict between the ‘Abbasid andFatimid dynasties. It is in the struggle for political authority and religiouslegitimacy that new and competing forms of expression took hold.In discussing the book’s themes and the discourses of which it is a part,Tabbaa refutes the essentialist traditions of some Orientalists, art historians,and even aestheticians that, while having seemingly different intentions, allportray Islamic art as separate or divorced from its history. They ignore orgloss over significant historical developments in the Islamic world, and thereforerepresent Islamic art, in all of its variety, as a homogenous genre, as theterm arabesque implies. Tabbaa highlights the epoch of the Sunni revival byrejecting the essentialist models and focusing on the period’s unique conflictsand changes. He argues that calligraphic, ornamental, and architecturalforms, in addition to being instruments of perceptual mediation, were engenderedwithin specific discourses to give symbolic support to certain claims toauthority and to establish a difference against challenging claims ...